Hostage : a novel - Mackintosh, Clare (Sourcebooks Landmark, 2021)
"A claustrophobic thriller set over twenty hours on one airplane flight, with the heart-stopping tension of The Last Flight and the wrenching emotional intensity of Room, Hostage takes us on board the inaugural nonstop flight from London to Sydney. Mina is trying to focus on her job as a flight attendant, not the problems of her five-year-old daughter back home, or the fissures in her marriage. But the plane has barely taken off when Mina receives a chilling note from an anonymous passenger, someone intent on ensuring the plane never reaches its destination. Someone who needs Mina's assistance and who knows exactly how to make her comply. It's twenty hours to landing. A lot can happen in twenty hours.."--